La pintura mural como medio artístico y reflexivo en la percepción pública en el cantón el guabo - Romero Pulla, Gislayne Kelly (Machala, 2025)
This Project analyzes how urban art is perceived in the cantón of El Guabo and its impacto n the cultural identity of the local community. Street art unquestionably encompasses several themes and social problems that arise in contemporary times, transforming them into artistic proposals directed to the public eye in masses, as a result of which this artistic manifestation has a direct impact on society and public space in different nuances. Historically, it has been used as a means of rebellious protest against social and political contexts where artists expressed their critical positions, most of them together with collectives in support of a single cause, an occurrence not very dissimilar to the context of El Guabo where much of its center is enriched by these artistic works, however, certain sectors are reluctant because of the stigmas of urban art. El Guabo is one of the most important cities in the province of El Oro, in recent years has gained increased cultural recognition which has allowed the intervention of several artists to capture an artistic imprint on its walls. These events represented a great rise to the notoriety of the city and the need to highlight what makes up its suburbs, thus providing a welcoming reception to the various artistic expressions that can be manifested. However, it is not a phenomenon that can be generalized for an entire city of approximately 26,635 inhabitants just three years ago, a time close to the peak of different and more diversified artistic expressions, which leads to the justification of this research and its singularities. Being a complex artistic medium, revealed above, the challenge is to create a direct impact on the inhabitants of this cocoa city, whose experience is a prelude to a favorable perspective on urban art in general, as well as a more personal and introspective perspective that debates the possible preconception of Street art. The proposal obtains a firm and concise structure of its elements and the subject matter it addresses. In it, a woman, symbol of the Guabeño charm, is observed proliferating from her long hair the leaves of the flagship fruit of the canton of El Guabo, foliage that exalts its prodigious fertile land. In her hand she gracefully and delicately lifts a bubble with a landscape in the background and a heron resting in admiration, connecting the inhabitants of the city with the coastal outskirts of the canton. The pink color plays a fundamental role in its placement, as it enhances and accentuates each element indeliberately. As a result, the work integrates and unifies the élan of mural art with an artistic proposal of cultural identity, making it a perfect artistic work for the environment in which it is inserted and the message it sends. “Allysa” is a mural made by a Guabeña for El Guabo, the connection of the community from her sketch to her last brushstroke is an experience of euphoria and fulfillment unique as an artist.
las hojas de la fruta insignia del cantón El Guabo, follaje que enaltece su prodigiosa tierra fértil. En su mano levanta con gracia y delicadeza una burbuja con un paisaje de fondo arrebolado y una garza reposando en su admiración, conectando a los habitantes dentro la ciudad con las afueras costeras del cantón. El color rosado juega un papel fundamental en su colocación, pues realza y acentúa cada elemento indeliberadamente. Como resultado, la obra integra y unifica el élan del arte mural con una propuesta artística de identidad cultural, convirtiéndolas en una obra artística perfecta para el entorno en el que se inserta y el mensaje que se busca transmitir. “Allysa” es un mural hecho por una guabeña para El Guabo, la conexión de la comunidad desde su bosquejo hasta su última pincelada es una experiencia de euforia y plenitud única como artista.
Keywords: ARTE MURAL; ARTE URBANO; IDENTIDAD CULTURAL; SOCIEDAD; EL GUABO